The costs of physical inactivity in the Czech Republic in 2008 - Maresova, Katerina (Journal of physical activity & health, 2014)
BACKGROUND: Several scientific studies estimate the burden of physical inactivity in different countries, yet in the Czech Republic, this kind of research is still missing. This paper represents one of the first attempts to quantify the costs of physical inactivity in the Czech Republic for 2008. METHODS: The analysis, based on scientific literature review, uses the comparative risk assessment methodology and applies it on data available in the Czech Republic. RESULTS: In 2008, the financial cost of physical inactivity to public health insurance companies was almost 700 million Kc, or 0.4%, of total healthcare costs. Furthermore, physical inactivity caused 2442, or 2.3%, of all deaths in 2008 and 18,065, or 1.2%, of all disability-adjusted life years in 2004. CONCLUSIONS: The costs of physical inactivity in the Czech Republic are considerable, yet slightly smaller than in other comparable studies. The obtained results could be used as an argument for policymakers when conceiving public or private health policy.
Keywords: pohybová aktivita; Health Care Costs; mortalita; Humans; lidé středního věku; Sedentary Behavior; prevalence; Cost of Illness; mladý dospělý; dospělí; Public Health; sedavý životní styl; veřejné zdravotnictví; Costs and Cost Analysis; lidé; náklady a analýza nákladů; mladiství; Mortality; Quality-Adjusted Life Years; náklady na zdravotní péči; podpora zdraví; osobní újma zaviněná nemocí; Adult; Middle Aged; Adolescent; Czech Republic; Health Promotion; Young Adult; kvalitativně upravené roky života; Prevalence; Motor Activity; Exercise; Česká republika; Leisure Activities; cvičení; volnočasové aktivity